Ellis-van Creveld syndrome in a neonate: a case report - Asif, Sana; Salahudeen , Akeel Ahamed; Nadeem, Ghazanfer; Abdul Sattar (Journal of the Pakistan Medical Association, 2023)
Ellis-Van Creveld Syndrome (EVC) is a rare genetic disorder with autosomal recessive inheritance, caused by mutations in two genes, EVC1 and EVC2 in the 4p16 chromosome. The exact prevalence of EVC is unknown and is estimated at approximately seven per million. It affects males and females equally. It is a constellation of four findings, including chondrodysplasia, polydactyly, ectodermal dysplasia, and congenital heart defects. Our case was unique as it had left inguinal hernia, short phallus, hyperpigmented scrotum, cryptorchidism, and other defining features of this syndrome. A multidisciplinary team managed this patient with regular follow up. Only six cases have been reported in Pakistan, and only one of them was reported in a neonate. This report highlights the importance of timely and proper multidisciplinary management of such disorders for better outcomes. It will also create awareness among medical professionals and will help them to identify promptly.